FINE ROOT BIOMASS, FOREST FLOOR AND NUTRIENT STATUS OF SOIL IN AN AGE SERIES OF TEAK PLANTATION IN DRY TROPICS - K. P. SAHU; SINGH , LALJI; M. K. JHARIYA (The Bioscan, 2013)
The present study was conducted in an age series of teak plantation in tropical environment at Barnawapara Wildlife Sanctuary, Chhattisgarh during the year 2011-2012. Total fine root biomass in the present study was between 4.80 t ha-1 and 9.81 t ha-1 and showed the decrease trends of fine root biomass with the age of the teak plantation. The forest floor biomass increased with the age of the teak plantation and the total forest floor biomass in the present study was between 2.19 t ha-1 and 2.66 t ha-1. Total nitrogen observed under soil in age series of teak plantation ranged from 0.083 to 0.143% for surface soil (0-10 cm) and 0.064 to 0.091% for lower layer soil (1020 cm). Total carbon was ranged from 1.124 to 1.736% for surface soil sample and 0.703 to 1.312% for lower layer soil sample. The concentration of available phosphorus (0-20 cm) under the 19 years old teak plantation and 33 years old teak plantation varied from 8.55 to 12.04 kg ha-1 and 13.74 to 12.06 kg ha-1, respectively. The availability of phosphorus in the soil of 23 years old teak plantation was found to be higher as 11.88 to 15.72 kg ha-1 than the other plantations. Whereas, it was recorded minimum in the 19 years old teak plantation. The result of available potassium for the soil were 314.07 to 335.48 kg ha-1, 382.21 to 266.47 kg ha-1 and 292.95 to 249.54 kg ha-1 under 19 years old teak plantation, 23 years old teak plantation and 33 years old teak plantation, respectively. The value of C, N and P% are higher in moderate age (23 years) plantation in comparison to value of K%, which found higher in the old age plantation (33 years).